Contextual drivers of energy demand and supply from renewable sources - Mattia De Rosa; Marta Meleddu; Manuela Pulina (Heliyon)
This study investigates the socio-economic and environmental drivers shaping renewable energy demand and supply within a meso-level setting (Italian regions, 2004–2020). Employing a panel vector error correction mechanism (PVECM) and an integrative biplot analysis, the research outcomes reveal a market equilibrium between demand and supply in the short and long run. Human capital accumulation is identified as pivotal in driving the renewable energy transition. Significant regional heterogeneities indicate challenges in achieving convergence towards sustainability and socio-economic development and well-being. Key empirical implications include enhancing education and vocational training to strengthen human capital and implementing tailored regional strategies for sustainable infrastructure development. These findings support policymakers in formulating targeted policies for a resilient, balanced energy future and addressing regional disparities in renewable energy adoption.